Reassembling the 'collective' in the face of "silenced machines": Tanta llKettan as a case of privatizing the public - Moustafa, Alaa (AUC Knowledge Fountain, 2020)
Tanta llKettan wel Zeyoot (trans. Tanta Flax and Oils Company) was a company established in Gamal AbdulNasser’s 1954 within the backdrop of a care-taking public sector. The company, emblematic of many public sector companies, got privatized as part of the larger neoliberal state vision, stemming with Anwar al-Sadat’s Infitah (Open Door) policies. These policies were embedded and solidified later within the nineties’ Economic Reform and Structural Adjustment Program policies package propagated by the International Monetary Fund and World Bank. With 2011’s Egypt’s utopic revolutionary imaginary and its moments of open-ended dreams, the labor movement appealed to court to revoke its privatization decision. In July 2011, Tanta llKettan got reinstated to the public sector, resulting in the labor movement’s entanglement in another series of struggles. This dissertation looks at how workers navigated various forms of power and asks what constituted Tanta llKettan’s movement to its workers. How can we narrate stories of Tanta's labor(ing) movement? How do different intensities of various spatiotemporal moments create and recreate events; and how do they affect the ways stories are told?